The prognostic value of the AgNOR parameter in human breast cancer depends on the pRb and p53 status. Issue 7 (25th June 2004) - Derenzini, M; Ceccarelli, C; Santini, D; Taffurelli, M; Treré, D
Abstract : Background: The amount of argyrophilic nucleolar organiser regions (AgNORs) represents a cell kinetics parameter used in tumour pathology for prognostic purposes. AgNOR expression is directly related to the rate of ribosome biogenesis, which has been recently shown to be controlled also by the tumour suppressor proteins pRb and p53. Aims: To ascertain the relative prognostic value of AgNORs and of pRb and p53 expression in breast carcinoma. Methods: This study was carried out on 335 human primary breast carcinomas with a median follow up time of 108 months. AgNORs were measured by morphometric analysis on sections that had been selectively silver stained; expression of p53 and phosphorylated and non-phosphorylated pRb forms was assessed by immunohistochemistry. Results: Patients were divided into groups with low (249) and high (86) AgNOR values; with normal (267) and mutated p53 (68); and with normal (256) and hyperphosphorylated or deleted pRb (79). Univariate analysis of disease free survival showed that AgNORs and the status of pRb and p53 were significantly related to the patients' clinical outcome. However, among the four groups characterised by different pRb and p53 status, the AgNOR parameter was not capable of distinguishing subgroups of patients with different clinical outcomes. Conclusions: These findings indicate that the prognostic value of the AgNOR parameter depends on the status of the tumour suppressor proteins pRb and p53, and it cannot be ascribed to the relation between AgNORs and the cell proliferation rate.